1986
DOI: 10.1073/pnas.83.17.6387
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a complementary DNA specific for human aromatase-system cytochrome P-450 mRNA.

Abstract: A cloned complementary DNA sequence has been isolated from a human placental cDNA library in the bacteriophage expression vector Agtll after screening with polyclonal antibodies against human placental aromatasesystem cytochrome P-450 (P-45Or.^). A single recombinant clone, XhAROM1, was characterized by its ability to generate a 3-galactosidase fusion protein that reacted independently with polyclonal antibodies raised against .-galactosidase and cytochrome P-450Arm and with monoclonal antibodies specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 35 publications
2
34
0
2
Order By: Relevance
“…Evans et al [26] reported the occurrence of three mRNAs (3.0, 2.7 and 2.4 kb) for human placental P-450ARoM. They dS0 isolated tW0 P-&&ROM cDNAs of different length and suggested that the two major mRNAs are formed by differential RNA processing [lo].…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al [26] reported the occurrence of three mRNAs (3.0, 2.7 and 2.4 kb) for human placental P-450ARoM. They dS0 isolated tW0 P-&&ROM cDNAs of different length and suggested that the two major mRNAs are formed by differential RNA processing [lo].…”
Section: Discussionmentioning
confidence: 99%
“…To provide a model in which to test antitumor efficacy of aromatase inhibitors, MCF-7 cells were transfected with the human aromatase cDNA (17). MCF-7Arom5 expresses high aromatase levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full-length human placental aromatase cDNA (17) was introduced into pcDNA3.0 and transfected into MCF-7. Clones were selected and screened for aromatase expression.…”
Section: Methodsmentioning
confidence: 99%
“…tant enzyme for the progression of estrogen-dependent breast cancer, because it catalyzes the final limiting step in the biosynthesis of estrogens from androgens (1)(2)(3)(4). The levels of aromatase activity and aromatase mRNA are significantly greater in breast cancer and surrounding adipose tissues than in nonneoplastic breast tissues (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%